The Cost of Visit-based Home Care for up to Two Weeks in the Last Three Months of Life: APilot Study of Community Care Based at a Hospice-at-home Service in South East of England. Issue 4 (1st October 2020) - Spiro, Stephen; Ward, Alison; Sixsmith, Judith; Graham, Anne; Varvel, Sue
ABSTRACT: The cost of visit-based community care based around a 24/7 hospice-at-home (HatH) service in the last 3 months of life was assessed. Thirty families completed a health and social carediary of at-home visits over two-weeks following contact with the HatH night service. Diaries captured 333 days of care provision, averaging 11 diary days per family, 708 health care professional and carer visits, lasting 604 hours at a cost of £20, 192 (24, 946). Hat H care, integrated with community support, seems an economic proposition but highlights the complexities of assessing cost of end of life care.